2016
DOI: 10.1186/s12968-016-0252-3
|View full text |Cite
|
Sign up to set email alerts
|

Age dependence of pulmonary artery blood flow measured by 4D flow cardiovascular magnetic resonance: results of a population-based study

Abstract: BackgroundIt was our aim to systematically analyze pulmonary artery blood flow within different age-groups in the general population using 4D flow cardiovascular magnetic resonance (CMR) in order to provide a context for interpreting results of future studies (e.g., in pulmonary hypertension) using this technique.MethodsAn age-stratified sample (n = 126) of the population of the city of Freiburg, Germany, underwent ECG-triggered and navigator-gated 4D flow CMR at 3 T of the pulmonary arteries and the thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
(37 reference statements)
4
20
1
Order By: Relevance
“…We performed a cross-sectional observational study of an age-stratified sample of the population of the city of Freiburg, Germany (for details see [ 14 ]). The cohort was established on the basis of data obtained from the German Civil Registration System.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a cross-sectional observational study of an age-stratified sample of the population of the city of Freiburg, Germany (for details see [ 14 ]). The cohort was established on the basis of data obtained from the German Civil Registration System.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it can be used to evaluate indices of RV systolic function from volume segmentation [ 11 ]. Despite its inherent potential to comprehensively assess right heart filling and associated pathologic conditions, most applications of cardiac 4D flow CMR, however, have focused on the left heart [ 12 , 13 ] or the pulmonary arteries [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main pulmonary artery of patients with pulmonary hypertension shows secondary morphological changes including dilatation that may induce vortical formation of the blood flow. In a general population-based study using 4D flow MRI, abnormal vortices occurred in the main pulmonary artery in 3% of subjects with no history of pulmonary hypertension [41]. The geometry of the main pulmonary artery dividing into the bilateral pulmonary arteries may influence the formation of an abnormal vortical flow even in healthy subjects.…”
Section: Pulmonary Hypertensionmentioning
confidence: 98%
“…Table 1 summarizes the selected clinical applications of 4D flow MRI in various vascular fields. Past studies have also demonstrated hemodynamics of normal cohorts, various hemodynamic changes in cardiovascular diseases, and comparisons before and after interventions for cardiovascular diseases [26,41,52,53]. This article focuses on the clinical application of 4D flow MRI in the field of the great arteries, including aortic diseases, adult congenital heart diseases (CHDs), and pulmonary hypertension.…”
Section: Clinical Application Of 4d Flow Mrimentioning
confidence: 99%
“…Population based pulmonary artery blood flow is unknown. In this prospective study, Wehrum et al [ 56 ] studied 126 age-stratified subjects (at least 20 subjects (10 M/10F) per decade) and found time-to-peak systolic antegrade flow was shorter and peak and average velocities and flow volumes were lower in older subjects. At the end of systole, retrograde flow in the main pulmonary artery was present in all but one subject.…”
Section: Cardiomyopathiesmentioning
confidence: 99%